Modeling stress-strain state of the section of human dental apparatus with the account of contact interaction between the teeth and their partial absence - S. S. Sherbakov; I. V. Koval; G. V. Gribovskii; M. M. Polestchuk; D. A. Padhaiskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
Complex interaction of incisors of the multi-element system “jaw – tooth – periodontium – enamel – dentinˮ is considered in the present work. The model was created on the basis of tomographic images taking into account previous studies of the human dental apparatus for a simplified model of three molars. The aim of the work is to determine the stress-strain states of the “jaw – periodontium – tooth – dentinˮ system for a different number of incisors and their location using three-dimensional computer finite-element modeling. The results of the study allow obtaining a more complete and accurate assessment of the state of the human dentofacial apparatus as a whole and each of its elements separately in order to improve the technologies and methods of prosthetics.